2012
DOI: 10.1177/1468796812449707
|View full text |Cite
|
Sign up to set email alerts
|

Are anti-Muslim feelings more widespread than anti-foreigner feelings? Evidence from two split-sample experiments

Abstract: This article tests the claim that anti-Muslim feelings are more widespread than general anti-foreigner feelings. It reports on two split sample experiments, in which a randomly selected part of the respondents evaluated statements for which the target group was identified as 'foreigners' and the other part evaluated the identical statements but with the target group identified as 'Muslims'. By using open-ended questions we are able to separate those respondents who had Muslims in mind when asked about foreigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 25 publications
3
37
0
5
Order By: Relevance
“…One major research study (Moore et al, 2008) found that media portrayals of Islam as 'dangerous, backward or irrational' and as being 'in opposition to dominant British values' were very common, while coverage of attacks on, or problems facing, Muslims had steadily declined. Such findings are supported by studies of public perceptions of Muslims across western countries (Dunn et al, 2007;Spruyt and Elchardus, 2012; see also Allen, 2010a). Allen (2010b) discusses how Barker's (1981) original discussion of 'new racism' referred to the shift away from biological markers as the basis for discriminatory processes, and he notes that:…”
Section: The Interplay Between Anti-muslim Racism and Immigrationmentioning
confidence: 69%
See 1 more Smart Citation
“…One major research study (Moore et al, 2008) found that media portrayals of Islam as 'dangerous, backward or irrational' and as being 'in opposition to dominant British values' were very common, while coverage of attacks on, or problems facing, Muslims had steadily declined. Such findings are supported by studies of public perceptions of Muslims across western countries (Dunn et al, 2007;Spruyt and Elchardus, 2012; see also Allen, 2010a). Allen (2010b) discusses how Barker's (1981) original discussion of 'new racism' referred to the shift away from biological markers as the basis for discriminatory processes, and he notes that:…”
Section: The Interplay Between Anti-muslim Racism and Immigrationmentioning
confidence: 69%
“…In particular, I try to articulate an understanding of racism that is sufficiently complex to be responsive to contemporary realities, without losing the important insights of writers such as Frantz Fanon (1967aFanon ( , 1967b on the consequences of colonial domination. A fuller understanding of race, migration control and immigration detention must also include consideration of colonialism as well as class and marginalized white ethnicity (Earle, 2014;Fekete, 2009;Phillips, 2008;Webster, 2008), the intersections between immigration control and Muslim identity (Allen, 2010a(Allen, , 2010bBravo López, 2011;Spruyt and Elchardus, 2012) and the gendered nature of immigration control (Hales and Gelsthorpe, 2012;Smith and Marmo, 2011). I examine each of these issues below.…”
Section: Introductionmentioning
confidence: 99%
“…Ford (2011) finds an 'ethnic hierarchy' in British immigration attitudes, with people being much less positive towards non-white compared to white immigration. Other studies show that people in Europe are generally more prone to oppose immigration from Muslim countries compared to immigration from other parts of the world (Strabac & Listhaug 2008;Spruyt & Elchardus 2012). Also, they prefer high-skilled over low-skilled immigrants (Hainmueller & Hiscox 2007), which according to Helbling and Kriesi (2014) can be traced to welfare concerns and beliefs about work ethic.…”
Section: Economic and Cultural Threatsmentioning
confidence: 99%
“…First, almost all larger immigrant minorities in Western Europe have a Muslim background (except for Indian people in Great Britain). When people are asked to think of immigrants, they tend to think about Muslims most of the time (Spruyt and Elchardus ; see also Strabac and Listhaug ). And several studies have shown that anti‐Muslim sentiment is closely related to other types of prejudice, like ethnocentrism (Van Bohemen et al.…”
Section: Methodsmentioning
confidence: 99%